Analisis Karakteristik Fisik Das Dengan SRTM 1 ARC Second Di Sungai Progo - A. Khomaini Fauzan (Jur. Teknik Sipil Fak. Teknik UMY, 2016)

(untitled)
The physical characteristics of the watershed is the basic variables that determine the hydrological processes in the watershed. Making the network of rivers and watersheds of the manual hardcopy using topographic maps take a long time and cost a very large, so we need a way to be able to save time and costs. Data Digital Elevation Model (DEM) is a digital data that describe the geometry of the shape of the earth's surface or part thereof which consists of a set of points coordinates of the sampling results. DEM data in this study using data from the Arc Second SRTM 1, this data is the latest version in which the DEM data has a smaller pixel size is Â± 30m 2 if compared to the previous version is Â± 90m 2 . The purpose of this study was to analyze the physical characteristics of the watershed Progo using DEM data SRTM 1 Arc Second and software ArcGIS. In this study, analysis of watershed delineation is obtained from the Watershed features, while networking or stream flow is obtained from the feature Flow Accumulation and Stream Order. Additional analysis in this study is a comparison of elevation data DEM and DEM reconditioning, in order to compare and adjust the DEM data of the topography in the field. The difference value 6.0585 km 2 watershed with the percentage of 0.2462% of the data from the agency. So that the method in this research can be used to determine the boundary of the watershed. The length of the main river 121.71 km with a difference in the value of 18.29 km, or 13.0665% of river length of BPDAS Serayu Opak Progo Progo and the difference of 6.71 km or 5.8348% of the flow of network data measurement from Badan Informasi Geospasial (BIG). The slope of the land acquired in Progo watershed area is 15.94%, so it can be categorized quite steep. Progo watershed land use is dominated by orchards, rice fields and upland settlements, with a total area reaches 2.294.492.959m 2 . As for the type of soil in the predominantly volcanic rocks mainly volcanic rocks parcel that reached broad 942.327.488,97m 2 .